Selective Abortion After Preimplantation Sex Selection: An Ethical and Legal Issue in Indonesia - Pujiyono, Pujiyono; Budiyanti, Rani Tiyas (Global Health Management Journal, 2018)
Background: The emerging of sex selection technology in Indonesia is sperm sorting, meanwhile sex selection with Preimplantation Genetic Diagnosis (PGD) methods is not widely used. The use of sperm sorting has bigger chance to fail than PGD, thus potentially cause ethical and legal problems that is selective abortion during pregnancy. The potency for selective abortion is enlarged by Indonesian law that permitting sex selection without distinction of medical and non-medical reasons. There is no special policy to regulate the selective abortion because of sex selection failure.  Aims: This study aims to find out the legal concept of selective abortion after preimplantation sex selection that appropriate to be applied in Indonesia.Methods: This research is normative research that use analytics method with legal approach and conceptual approach. The research material consists of primary legal material (legislation about sex selection and abortion in Indonesia), secondary legal materials (legal journals, law books, and legal proceedings), and also non-legal materials (journals, books, and health proceedings about sex selection and abortion).Results: In Indonesia meanwhile in general, abortion is permitted for pregnancy with medical indication and rape victim. Through a statue approach in Indonesia, selective abortion after preimplantation sex selection can be implemented for strong medical reasons. While the failure for non-medical reasons can’t be aborted. This regulation contrary with ethics, morals and religion. Selective abortion should not be done because of preimplantation sex selection failure either medical or non-medical reasons. Conclusion: Selective abortion after preimplantation sex selection both medical and non medical reason contrary with moral, ethical, and religion. Indonesia needs to regulate further policy about selective abortion if there is a failure of preimplantation sex selection.